2001
DOI: 10.1053/jhep.2001.20642
|View full text |Cite
|
Sign up to set email alerts
|

Hla Class Ii Genes Determine the Natural Variance of Hepatitis C Viral Load

Abstract: The aim of this study was to investigate the relationship between human leukocyte antigen (HLA) class II genes and the natural fluctuations in hepatitis C viral load in a homogeneous patient population. The study group consisted of 57 viremic (hepatitis C virus [HCV] 1b) women for whom HLA class II DRB1 and DQB1 haplotyping, virologic, histologic, and biochemical markers of disease activity were available. All patients were infected with HCV 1b from the same source of hepatitis C-contaminated anti-D immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 57 publications
3
47
1
Order By: Relevance
“…This is an important finding as, to date, we have not come across any report that has demonstrated the association of an HLA-DRB1-DQB1 haplotype with persistence of HCV in Pakistani patients. However, Fanning et al (2001) reported a positive response to IFN therapy in patients from Ireland with the haplotype HLA-DRB*0701-DQB1*02, again indicating the need to conduct such studies in ethnically different patient populations. In agreement with the data of Correa et al (2002), we also found this haplotype to be the most common in non-responders and in linkage disequilibrium in our population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important finding as, to date, we have not come across any report that has demonstrated the association of an HLA-DRB1-DQB1 haplotype with persistence of HCV in Pakistani patients. However, Fanning et al (2001) reported a positive response to IFN therapy in patients from Ireland with the haplotype HLA-DRB*0701-DQB1*02, again indicating the need to conduct such studies in ethnically different patient populations. In agreement with the data of Correa et al (2002), we also found this haplotype to be the most common in non-responders and in linkage disequilibrium in our population.…”
Section: Discussionmentioning
confidence: 99%
“…In seropositive individuals exhibiting spontaneous viral clearance, the CD4 + T-cell response is mostly against non-structural proteins (NS3, NS4 and NS5) with the predominant response being against NS3 (Lloyd et al, 2007). An epitope in the NS3 region shows high affinity for HLA-DR, indicating the possible involvement of HLA class II in virus clearance (Fanning et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…71,72 Studies of HCV progression or severity of disease A total of 44 studies were found to address the topic of host genetics and HCV progression, severity or activity of disease, and have largely been inconsistent. 16,18,27,29,32,34,37,39,47,[68][69][70]80, There is a trend with DRB1*11 alleles and less severe liver disease. Asti 68 reported an association between DRB1*1201 with less severe liver disease (OR not reported) as well.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%
“…Fanning et al (2001) reported that individuals who possess the alleles DRB1*0701 and/or DQB1*0201 have a relatively stable viral load over time. Also DRB1*07 and DQB1*02 were found by Wawrzynowicz-Syczewska et al (2000) in responsive patients and Jiao and Wang (2003) found a higher response rate to IFN in patients with the HLA-DRB1*07 allele where Martinetti et al (2006) reported that DRB1*13 allele was significant in protection from chronic HCV especially the protection from vertical transmission in infants born to HCV positive mothers.…”
Section: Discussionmentioning
confidence: 99%